Representasi Dampak Hoax Pada Film Budi Pekerti Karya Wregas Bhanuteja : Konten Viral - Syarifah, Arneta; Urfan, Noveri Faikar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Misusing social media can make the process of verifying information abandoned and the information or news consumed by the public even more misleading. This study will discuss the representation of the impact of Hoaxes shown in the film Budi Pekerti by Wregas Bhanuteja. The aim is to analyze how the representation of the effects of Hoaxes depicted through viral content in the movie raises social issues today. This study uses a qualitative approach that is descriptive and uses the Roland Barthes semiotic analysis method through three stages that are presented in analyzing the meaning of signs, namely, the meaning of denotation, connotation, and myth, with data collection techniques, namely non-participant observation and documentation in the form of screen capture. The results of this research in the film Budi Pekerti present the impact of Hoaxes that can lead people to negative perceptions and negative comments quickly, cause cyberbullying and damaged reputation, cause the phenomenon of cancel culture, cause a domino effect and truth that is no longer important in a person's life. This research also provides awareness that you must be wise and ethical in social media by not being easily incited, finding out the truth first, not behaving impulsively, and having a sense of empathy.